Rancang Bangun dan Sosialisasi Alat Perontok Jagung untuk Meningkatkan Efisiensi Pemipilan Pasca Panen Jagung serta Mendukung Pertanian Berkelanjutan di Kismantoro, Kabupaten Wonogiri - Purwanta; Pulung Dwi Swastanto (Direktorat Pengabdian kepada Masyarakat, 2024)
Kismantoro District is located in Wonogiri Regency, Central Java. It has a tropical climate and highland topography that supports the agricultural sector. These conditions create an ideal environment for agricultural activities with sufficient rainfall and relatively cool temperatures. Farmers in Kismantoro take advantage of natural conditions to grow crops, thereby producing various types of food crops, horticulture, and other agricultural commodities. The dominance of agricultural land is a characteristic of community life and the local economy in Kismantoro. Every year this region experiences three harvest periods, namely two rice harvest periods and one corn or soybean harvest period. To optimize the management of agricultural products in Lemahbang Village, the UGM KKN-PPM Team carried out a work program in the form of making corn threshers for farmer groups in Lemahbang Hamlet. This program aims to help farmers speed up the process of separating corn kernels from cobs (jangle) which previously was still done manually using hands, as well as introduce the development of appropriate technology to support sustainable agriculture in Kismantoro District. The methods used in collecting data for this activity were observation, interviews, study of literature, and recording. Apart from that, sampling was carried out using a purposive sampling method, and data analysis techniques were carried out using mixed methods research (quantitative and qualitative). In this program, socialization and guidance will also be carried out regarding how to use and care for corn threshers, as well as the introduction of other appropriate agricultural technologies to the Lemahbang Village Farmers Group. It is hoped that the application of Science and Technology (IPTEK) provided in this activity can optimize the agricultural sector in Lemahbang Village and support sustainable agriculture. Keywords: Lemahbang Village, Corn Thresher Tools, Socialization.